DRUGS AND SUBSTANCE ABUSE IN KENYAN SECONDARY SCHOOLS: IS IT A REALITY?. - Ngesu, Lewis M. (IJRDO- Journal of Educational Research, 2017)
Drug abuse has become a global phenomenon affecting almost all countriesthough the degree and individuality effects and impacts show a discrepancy depending onthe country in question. Kenya has not escaped the phenomena, drug abuse haspermeated all stratums of Kenyan people; many of the Kenyan youths, especially those insecondary schools, are falling prey to drug and substance abuse. This has ruined theirlife as a result of addiction. Today it has become an African problem to the extent that amonthly hardly passes without media reports on large quantities of drugs having beenintercepted in a number of African cities and towns. The results of the study indicatedthat students abused drugs for varied reasons and the commonly abused drugs werealcohol, bhang, miraa, tobacco and kuber. The study recommended that guidance andcounseling in schools be enforced and that strict disciplinary measures be enforced byteachers to curb the vice. Policy makers should also focus their efforts on addressingadministrative disparities of principals’ leadership capacities across urban, suburbanand rural setting